Predictors of Low Birth Weight Neonates Delivered in a Hospital of Rupandehi, Nepal - Kachapati, Anuja; Lamichhane, Kavita; Gurung, Saraj; Chaudhary, Nagendra; Bhandari, Sharmila; GC, Narayan Bahadur; Sharma, Deepanjali (Journal of Universal College of Medical Sciences, 2022)
INTRODUCTION Low birth weight has been deﬁned by World Health Organization (WHO) as weight at birth of <2500 grams (5.5 pounds). Low birth weight is more common in developing than developed countries. Intrauterine growth restriction, prematurity or both cause low birth weight. It contributes to a range of poor health outcomes and it is closely associated with fetal and neonatal mortality and morbidity, inhibited growth and cognitive development, and Non-communicable Diseases (NCDs) later in life. Low birth weight infants are about 20 times more likely to die than heavier infants. MATERIAL AND METHODS A cross-sectional design was used to ﬁnd out the prevalence and predictors of low birth weight among 327 singleton neonates delivered in a Universal College of Medical Sciences, Teaching Hospital, Bhairahawa, Nepal by using Enumerative sampling technique. Semi-structured, pre-tested interview and record report was used to collect data and analyzed by using descriptive and inferential statistics with SPSS version 16. RESULTS The study ﬁndings revealed that the prevalence of low birth weight is 28.5% and there is statistically signiﬁcant association between parity (p= <0.000), mode of delivery (p= 0.001), ANC visit (p= 0.016), iron supplement (p=<0.000), tablet calcium (p=<0.000), tablet albendazole (p=0.023), food taboos (p= 0.058), rest at night (0.000), alcohol (0.015) during pregnancy parity (p= <0.000), mode of delivery (p= 0.001), ANC visit (p= 0.016), and low birth weight neonates. CONCLUSION The study concluded that the factors those were associated with low birth weight, which can be prevented at pregnancy period through good prenatal care and intervention programs such as health education on diet, rest, time to time check up, taking medicines, early identiﬁcation of complication.